Mobilidades habitacionais: práticas e fluxos de saídas dos moradores nos residenciais Juraci Magalhães e Miguel Arraes - Abreu, Josileine Araújo de (2015)
This thesis aims to investigate the residents outflow from Juraci Magalhães and Miguel Arraes housings, highlighting the main issues that emerge from this context. The research proposes to understand what does the searching mobility for new homes, existing inside the residential, tell us about the reinvention and creativity capacity of the residents. And what elements these mobility practices bring to think about the dynamic complexity of living on the outskirts of the city. A field survey was conducted from 2013 to 2015, using an unsystematic approach in both residential Juraci Magalhães and Miguel Arraes, located in significant neighborhoods that shape inequality and urban segregation in the city’s landscape, specifically in the territory of Grande Bom Jardim in Fortaleza-CE. The chains of thought are the narratives and daily practices of the current and former residents of both housing. Different routes and mediation were used to gather the field data, informal interviews recorded in field diaries, as well as an assembling of a photo archive. The research demonstrates how the apartment negotiations end up being shared and incorporated into the residents’ life as practices to reduce everyday life’s difficulties. Through this research it was possible to observe how the residents of the suburbs are often rebuilding and giving new meanings to the idea of citizenship from their urgent material conditions of life. Urban transformations set the individuals as producers and consumers of their cities and thus they are constantly managing their emergencies under the most diverse conditions, as housing, job market and the access to public and private services. These conditions impact directly in citizens’ life.